2023
DOI: 10.1021/acs.chemmater.3c00814
|View full text |Cite
|
Sign up to set email alerts
|

Defect Chemistry of Spinel Cathode Materials─A Case Study of Epitaxial LiMn2O4 Thin Films

Abstract: Spinels of the general formula Li 2−δ M 2 O 4 are an essential class of cathode materials for Li-ion batteries, and their optimization in terms of electrode potential, accessible capacity, and charge/discharge kinetics relies on an accurate understanding of the underlying solid-state mass and charge transport processes. In this work, we report a comprehensive impedance study of sputter-deposited epitaxial Li 2−δ Mn 2 O 4 thin films as a function of state-ofcharge for almost the entire tetrahedral-site regime (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 64 publications
2
17
0
Order By: Relevance
“…The remaining portion of the transmission line is identical to an ideal open Warburg element W o , which describes the impedance transition from semi-infinite to finite-space diffusion with characteristic phase angles of 45° and 90°, respectively. In our previous studies on Li 1− δ CoO 2 and Li 2− δ Mn 2 O 4 , 1,2 we have shown that the diffusional impedance of real intercalation electrodes can be fitted with an anomalous finite-space diffusion element embedded in the impedance analysing software EC-Lab (Biologic, France), which is closely related to the anomalous open Warburg element proposed by Bisquert. 41 The corresponding impedance expression readswith a nonideality parameter 0 ≤ α ≤ 1.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The remaining portion of the transmission line is identical to an ideal open Warburg element W o , which describes the impedance transition from semi-infinite to finite-space diffusion with characteristic phase angles of 45° and 90°, respectively. In our previous studies on Li 1− δ CoO 2 and Li 2− δ Mn 2 O 4 , 1,2 we have shown that the diffusional impedance of real intercalation electrodes can be fitted with an anomalous finite-space diffusion element embedded in the impedance analysing software EC-Lab (Biologic, France), which is closely related to the anomalous open Warburg element proposed by Bisquert. 41 The corresponding impedance expression readswith a nonideality parameter 0 ≤ α ≤ 1.…”
Section: Resultsmentioning
confidence: 89%
“…For further investigations, we therefore resort to impedance measurements, as established in our previous studies on Li 1− δ CoO 2 and Li 2− δ Mn 2 O 4 . 1,2 This virtually eliminates the effect of background currents and allows us to extract not only the volume-specific chemical capacitance C V chem ( i.e. , differential capacity), but also the charge transfer resistance R ct , the ionic conductivity σ ion and the Li chemical diffusion coefficient D̃ as a function of SOC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Basically, in ionic solids chemical diffusion is ambipolar. , In the present case, Li vacancies and holes have to be considered as relevant defects . In general, both species contribute to the chemical diffusivity.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, the conductivity of electronic charge carriers is orders of magnitude higher than that of ionic charge carriers. In case the concentration of electronic charge carriers is much higher than the vacancy concentration, we can write in approximation , D chem = D V = D tracer / f V where D V is the diffusivity of the vacancies and f V is the mole fraction of the vacancies. That means chemical diffusivities are higher than tracer diffusivities divided by the mole fraction of vacancies.…”
Section: Resultsmentioning
confidence: 99%